Implementation of World Customs Organization security and professional training standards: the Ukrainian experience - Павленко, О. О. (Pedagogy of Higher and Secondary Education, 2012)
Pavlenko O. O. Implementation of World Customs Organization security and professional training standards: the Ukrainian experience. In the article (using the Ukrainian experience) there are considered problematic aspects of implementation of international standards in the field of international transit, which concern safety standards and world trade facilitation SAFE Framework of Standards as well as training and professional development of specialists in foreign economic activity.